2021
DOI: 10.3389/fnut.2021.667695
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus ATCC 4356 Alleviates Renal Ischemia–Reperfusion Injury Through Antioxidant Stress and Anti-inflammatory Responses and Improves Intestinal Microbial Distribution

Abstract: Background: Ischemia–reperfusion injury (IRI) is one of the main causes of acute kidney injury. Our previous results have shown that anti-oxidative stress decreased in the renal IRI model. This study aimed to investigate the effect of Lactobacillus acidophilus ATCC 4356 on oxidative stress, inflammation, and intestinal flora in renal IRI.Methods: The model of renal IRI was established by cross-clamping the renal pedicle with non-traumatic vascular forceps. H&E staining was applied to observe the damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The gut flora is critical in the process of IRI. Specific bacteria, such as Lactobacillus acidophilus , alleviate renal IRI by improving intestinal microbial distribution and anti-inflammatory responses [ 34 ]. Bifidobacterium bifidum PRL2010 can inhibit the adhesion of pathogens and enhance the host innate immunity response, thereby attenuating intestinal IRI [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gut flora is critical in the process of IRI. Specific bacteria, such as Lactobacillus acidophilus , alleviate renal IRI by improving intestinal microbial distribution and anti-inflammatory responses [ 34 ]. Bifidobacterium bifidum PRL2010 can inhibit the adhesion of pathogens and enhance the host innate immunity response, thereby attenuating intestinal IRI [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . first explored the relationship between ATCC 4356 and renal ischemia-reperfusion injury (IRI) [ 67 ]. They found that L. acidophilus ATCC 4356 alleviated renal IRI through antioxidant stress and anti-inflammatory responses and improved intestinal microbial distribution in renal IRI mice.…”
Section: Biological Functions Of L Acidophilusmentioning
confidence: 99%
“…In the following treatment with ATCC 4356, the levels of anti-inflammatory factors (IL-4 and IL10) were upregulated, whereas the levels of pro-inflammatory factors (IL-1β, IL-8, TNF-α and IFN-γ) were downregulated. In addition, renal tissue apoptosis in IRI mice was reduced [ 67 ].…”
Section: Biological Functions Of L Acidophilusmentioning
confidence: 99%
“…In addition, administration of Bifidobacterium bifidum BGN4 significantly reduced IRI-induced other changes in the colonic microenvironment, including effects on colonic epithelial cell permeability, apoptosis, and infiltration of neutrophils and pro-inflammatory macrophages ( Yang et al., 2021 ). Lactobacillus acidophilus ATCC 4356 attenuates renal IRI and improves gut microbial distribution through anti-oxidative stress and anti-inflammatory responses ( Zhang et al., 2021b ).…”
Section: Gut Microbiota In Renal Irimentioning
confidence: 99%